2021
DOI: 10.4194/trjfas19303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Probiotic-Fermented Feed Addition and LaserFiring to Accelerate Mature Broodstocks and Seed Productions of African Catfish (Clarias gariepinus)

Abstract: This study aimed to determine the effects of fermented feed using probiotics and laser-firing to accelerate the mature broodstocks and seed productions of African catfish (Clarias gariepinus). Fish has used male and female broodstocks of catfish. The method was used a completely randomized design with three treatments: unfermented feed as control, probiotic-fermented feed (PFF), and probioticfermented feed+laser firing (PFF+Li). In the first study, a laser-firing dose of 1.125 Joule was performed on fish brood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Female rainbow trout that ingested commercial probiotic 'Bio-Aqua' (containing 8 bacterial strains or species) at 4 × 10 9 CFU kg −1 diet twice daily demonstrated higher absolute and relative Fec, FR, HR, and egg survival after 8 weeks [38]. Similarly, combined probiotics (5 bacteria and 2 yeasts) administered to female Clarias gariepinus (African catfish) broodstock fishes at dose of 5 mL kg −1 for 31-41 days and laser firing treatment at 1.125 Joule revealed that the probiotics treatment accelerated gonadal maturation [195].…”
Section: Femalementioning
confidence: 90%
“…Female rainbow trout that ingested commercial probiotic 'Bio-Aqua' (containing 8 bacterial strains or species) at 4 × 10 9 CFU kg −1 diet twice daily demonstrated higher absolute and relative Fec, FR, HR, and egg survival after 8 weeks [38]. Similarly, combined probiotics (5 bacteria and 2 yeasts) administered to female Clarias gariepinus (African catfish) broodstock fishes at dose of 5 mL kg −1 for 31-41 days and laser firing treatment at 1.125 Joule revealed that the probiotics treatment accelerated gonadal maturation [195].…”
Section: Femalementioning
confidence: 90%
“…Thus, the use of the probiotic "Subtilis" as such a stimulant, has been shown to increase the survival rate of eggs, embryos and larvae, reduce mortality in the larval stage of development, increase viability in the early stages of ontogenesis, as well as improve natural immunity [15]. In addition, there are also publications on the effects of probiotics on the reproductive ability of fish such as Nile tilapia Oreochromis niloticus [16], oil catfish Ompok pabda [17], African catfish Clarias gariepinus [18] and European eel A. Anguilla [19].…”
Section: Introductionmentioning
confidence: 99%